REGULATION (EU) NO. 2024/1689 AND LAW NO. 8/1996 ON COPYRIGHT. LEGISLATIVE, ECONOMIC, AND SOCIAL IMPACT - Ileana Ioana BÎLBĂ (Challenges of the Knowledge Society, 2025)
PwC studies estimate that the integration of AI into the economy could generate a global impact of up to $15.7 trillion by 2030, with other studies limiting this figure to $13 trillion. China and North America are expected to be the main beneficiaries, accounting for around 70% of the economic growth generated by AI. Europe, in comparison, is estimated to benefit from only $2.5 trillion, representing around 16% of global growth. Digital data is identified as a key asset and a major source of intellectual property revenue. Complying with the requirements of the regulation will generate additional costs. However, the long-term benefits are expected to outweigh these costs. Investments in compliance will also stimulate the development of new technologies and services to help companies comply. From a national legislation point of view, it will need to adopt European legislation and transpose Regulation 2024/1689 into a new law in Romania that harmonizes the legislation. In this study I will analyze the legislative, social and economic impact of the first regulation of AI through Regulation (EU) 2024/1689 at the EU level, then at the Romanian level and how it impacts Law no. 8/1996 and national copyright legislation.